Moderate-to-vigorous physical activity does not improve mortality in type 2 diabetes patients with severe abdominal aortic calcification. - Chang Sheng; Yacheng Xiong; Pu Yang; Wei Wang (PLoS ONE)
Background The impact of moderate-to-vigorous physical activity (MVPA) on all-cause mortality in type 2 diabetes (T2D) patients with severe abdominal aortic calcification (SAAC) remains unclear. Methods We analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2013-2014, including T2D patients aged 40 years and older. AAC was assessed using the Kauppila scoring system, with SAAC defined as a score >6. Self-reported MVPA was categorized based on weekly minutes of activity. The weighted Cox regression model was used to investigate risk associations. Results Among the weighted sample of 20,328,606 T2D participants, 16.39% had SAAC. SAAC was significantly associated with increased all-cause mortality (HR 2.57, 95% CI 1.52-4.35) after adjusting for confounders. MVPA did not significantly reduce mortality risk in patients with SAAC (HR 1.00, 95% CI 0.40-2.49). Conclusion SAAC is a robust predictor of mortality in T2D patients, and MVPA does not improve mortality outcomes in this high-risk group. Future studies should conduct more detailed subgroup analyses to identify the specific indications for MVPA.